Protection of Human Rights Against Women in an International Legal Perspective - Kastiady, Salvia Salsabila Putri; Rajib, Rayi Kharisma; Qoiri, Mutmainah Nur; Salikin, Zulfikar Ahmad Nur (International Law Discourse in Southeast Asia, 2024)
The protection of human rights for women has been a central issue in international law, reflecting the evolving recognition of gender equality and the need to address systemic inequalities. Historically, women have been marginalized in both legal and societal structures, facing discrimination, violence, and economic disparity. However, over the past century, a series of international conventions, treaties, and declarations have sought to safeguard women's rights globally. Notably, the Universal Declaration of Human Rights (UDHR), the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), and various regional instruments have played pivotal roles in shaping legal norms that promote gender equality and protect women from abuses. Despite these legal frameworks, challenges persist in the effective implementation and enforcement of women's rights protections. Cultural, political, and socio-economic barriers continue to obstruct the realization of gender equality in many regions, and women often remain vulnerable to violence, exploitation, and discriminatory practices. The international legal system, through the work of organizations such as the United Nations, has made strides in encouraging state accountability and establishing standards for the treatment of women, but gaps in enforcement mechanisms, state sovereignty, and varying cultural norms complicate the protection process. This paper explores the international legal frameworks designed to protect women's human rights, evaluates the effectiveness of these mechanisms, and examines the ongoing obstacles to achieving comprehensive gender equality. The study highlights the need for continued advocacy, stronger enforcement, and collaboration among global institutions to advance the protection of women's rights and ensure their full participation in all spheres of life.